2020
DOI: 10.5194/egusphere-egu2020-7590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-time discrimination of earthquake foreshocks and aftershocks

Abstract: <p>Immediately after a large earthquake, the main question asked by the public and decision-makers is whether it was the mainshock or a foreshock to an even stronger event yet to come. So far, scientists can only offer empirical evidence from statistical compilations of past sequences, arguing that normally the aftershock sequence will decay gradually whereas the occurrence of a forthcoming larger event has a probability of a few per cent.</p><p>We analyse the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…This interpretation is also consistent with recent observations of the foreshock sequences before the 1999 Izmit and 1999 Hector Mine mainshocks (Ellsworth & Bulut, 2018; Yoon et al, 2019). Finally, Figure S8 shows that the foreshock b values are lower than those of aftershocks, which is generally consistent with recent observations in other regions (e.g., Gulia & Wiemer, 2019; Tamaribuchi et al, 2018). However, we only applied template matching to the foreshock sequence, not the aftershock sequence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This interpretation is also consistent with recent observations of the foreshock sequences before the 1999 Izmit and 1999 Hector Mine mainshocks (Ellsworth & Bulut, 2018; Yoon et al, 2019). Finally, Figure S8 shows that the foreshock b values are lower than those of aftershocks, which is generally consistent with recent observations in other regions (e.g., Gulia & Wiemer, 2019; Tamaribuchi et al, 2018). However, we only applied template matching to the foreshock sequence, not the aftershock sequence.…”
Section: Discussionsupporting
confidence: 90%
“…The measured b value for foreshocks is lower than the value (0.96) of the aftershocks (Hauksson et al, 2010), which is also consistent with what we observed for catalog aftershocks with first 120 days (0.80, Figure S7). To verify whether our observation fits into the scenario of varying b values for foreshocks and aftershocks (Gulia & Wiemer, 2019), we applied a sliding window to measure b value using a constant number of 200 events by considering a time‐dependent Mc(t) (Hainzl, 2016). All 666 detected foreshocks were used for the foreshock window, while only ~2,730 catalog aftershocks within first 4 months from the waveform relocated catalog (the updated 1981–2018 catalog) were used for the aftershock period.…”
Section: Resultsmentioning
confidence: 95%
“…To monitor the potentially changing stress field following the mainshock, we calculated the b value time series of the ongoing sequence and compared it to the background value for the Salt Lake Valley area. Gulia and Wiemer (2019) proposed that time‐varying b value analysis can help identify whether ongoing earthquakes in a sequence are aftershocks of an earlier large event or foreshocks of a mainshock yet to occur. We experimented with different catalog subsets, magnitude cut‐offs, and time windows as described in Text S3.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…We experimented with different catalog subsets, magnitude cut‐offs, and time windows as described in Text S3. Our methodology followed Gulia and Wiemer (2019) but with some variation, for instance in the use of a relatively large area to calculate the background b value because of the low historical rate of seismicity in the Magna region. We found that in the hours following the mainshock, the b value did decrease from the background level of ~0.8 to ~0.4, potentially signaling that these events were foreshocks.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation